Numerical Investigation of Steel Section Remaining Tensile Capacity During SMAW Welding - Mushthofa, Malik (Universitas Muhammadiyah Surabaya, 2024)
This study investigates a method for calculating the remaining axial tension capacity of thin steel sections during Shielded Metal Arc Welding (SMAW) under load. This necessitates a method to address situations where welding operations must be performed on structures already experiencing stress. Thin sections are particularly susceptible to the elevated temperatures associated with welding. To address this challenge, simulations were utilized to model the effect of the welding heat on thin sections. The simulations considered the temperature rise experienced by each segment within the section. This rise led to a reduction in yield strength, ultimate strength, and elastic modulus for each segment. Subsequently, the partial tension capacity for each segment was calculated based on its area and the reduced strength properties. Finally, the remaining axial tension capacity was determined by summing the tension capacities of all segments. The results revealed a noteworthy correlation between welding parameters and the remaining tension capacity. Higher welding currents were associated with a greater loss of tension capacity, while faster welding speeds resulted in minimizing this loss. The scenario employing the lowest welding current and highest welding speed yielded the most favorable outcome, with the remaining tension capacity reaching 76%, 85%, and 89% for sections of 40.40.4, 50.50.5, and 60.60.6, respectively. Conversely, employing the highest welding current and slowest welding speed significantly reduced the remaining axial tension capacity until there were only 28%, 50%, and 66% left for the respective sections.